The Effect of Liquidity Ratios, Profitability Ratios, and Solvency to Value Ratio Company Studies on Sector Companies Consumer Goods Industry Listed on IDX Period 2018-2021 - Eka Yusania Viranda; Tony Antonio; Agus Arman (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
This study examines the effect of the company's liquidity, profitability, and solvency ratios on company value and company size is used as a control variable. Using the Purposive Sampling method with a total sample of 184 business entities in the consumer goods industry sector in Indonesia for the 2018-2021 period. The data analysis technique uses multiple linear regression analysis with the help of the SPSS 26 program. The findings showed that the liquidity ratio had no impact on the value of the company, while the ratio of profitability and solvency had a significant influence on the value of the company according to the hypothesis built in the study. The size of the company proved to significantly affect the value of the company. The implication of this research is that investors can use financial ratio analysis to make decisions before investing. Companies must also pay attention to their financial performance if they want to get investment funds. Large-scale companies usually have a large number of assets so that they can generate large profits, this is what can increase the value of the company.